A "estética do limite" em Eugenio Trías (La "estética del límite" en Eugenio Trías) - Dimas, Samuel (Cauriensia, 2023)
The split presented by Eugenio Trías’s "philosophy of the limit" leads us to a triadic movement of Hegelian influence, in which man appears as a frontier being (borderline reality) in exile from his spiritual foundation. The manifestation of the Mystery of the Spirit in the sensitive and historical reality takes place through the mediation of symbolic reason in two ways: in the aesthetic configuration of the world, carried out by art; in the revelation of the sacred, carried out by religion.